Analytical modelling of one cage rotor induction motor for electric submersible pumps - Farhad Rezaee‐Alam; Abbas Nazari Marashi; Abolfazl Dehafarin; Khalil Kanzi; Sam Roozbehani (IET Electric Power Applications, 2022)
Abstract A new hybrid analytical model (HAM) based on conformal mapping (CM) method and magnetic equivalent circuit (MEC) model is presented in this paper for electromagnetic modelling of cage rotor induction motors (CRIMs) used in electric submersible pumps (ESPs). For every operating point, the iron parts are modelled with a non‐linear MEC model to calculate the equivalent virtual currents, which represent the influence of magneto motive force (MMF) drops and MMF sources in stator and rotor cores. The effects of the equivalent virtual currents on the air‐gap magnetic field are then considered using the CM method and Hague's solution. This approach for calculating the air‐gap field is also used to prepare a 3‐D lookup table (3‐D LUT) for each element of inductance matrix and derivative of inductance matrix in terms of rotor position. These LUTs are then used for transient modelling and analysis of CRIM under no‐load and loading conditions. The accuracy of proposed HAM is validated by comparing the results obtained through HAM with corresponding results obtained from finite element method and experiment set‐up.